Social Connectivity in America: Changes in Adult Friendship Network Size From 2002 to 2007 - Hua Wang; Wellman, Barry (The American behavioral scientist (Beverly Hills), 2010)
There is some panic in the United States about a possible decline in social connectivity. The authors used two American national surveys to analyze how changes in the number of friends are related to changes in Internet use. The authors found that friendships continue to be abundant among adult Americans between the ages of 25 to 74 and that they grew from 2002 to 2007. This trend is similar among Internet nonusers, light users, moderate users, and heavy users and across communication contexts: offline, virtual only, and migratory from online to offline. Heavy users are particularly active, having the most friends both online and offline. Intracohort change consistently outweighs cohort replacement in explaining overall growth in friendship.